2013
DOI: 10.1371/journal.pone.0067994
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Exerts Greater Bacterial Clearance but No Modification of Host Lung Gene Expression Profiling: A Mouse MRSA Pneumonia Model

Abstract: BackgroundLinezolid (LZD) is beneficial to patients with MRSA pneumonia, but whether and how LZD influences global host lung immune responses at the mRNA level during MRSA-mediated pneumonia is still unknown.MethodsA lethal mouse model of MRSA pneumonia mediated by USA300 was employed to study the influence of LZD on survival, while the sublethal mouse model was used to examine the effect of LZD on bacterial clearance and lung gene expression during MRSA pneumonia. LZD (100mg/kg/day, IP) was given to C57Bl6 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Akinnusi et al (2011) did not observe a significant difference in IL-6 or MCP-1 concentration in BALF between LZD- and vancomycin-treated mice. Chen et al (2013) found that LZD therapy significantly decreased BALF protein concentration and levels of cytokines, including IL-6, IL-1β, IFN-γ, and IL-17. With LZD treatment, no abscesses formed, less lung edema occurred, and fewer inflammatory cells were observed compared with the control group.…”
Section: Introductionmentioning
confidence: 92%
“…Akinnusi et al (2011) did not observe a significant difference in IL-6 or MCP-1 concentration in BALF between LZD- and vancomycin-treated mice. Chen et al (2013) found that LZD therapy significantly decreased BALF protein concentration and levels of cytokines, including IL-6, IL-1β, IFN-γ, and IL-17. With LZD treatment, no abscesses formed, less lung edema occurred, and fewer inflammatory cells were observed compared with the control group.…”
Section: Introductionmentioning
confidence: 92%
“…Linezolid inhibits the secretion of proinflammatory mediators resulting in diminished chemotaxis of immune cells into the airways [96][97][98]. In particular, neutrophil migration, which is a hallmark of ARDS, is inhibited [97,99]. Additionally, linezolid restores neutrophil effector mechanisms like phagocytosis and killing of pathogens while it suppresses phagocytosis in macrophages [100,101].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Additionally, linezolid restores neutrophil effector mechanisms like phagocytosis and killing of pathogens while it suppresses phagocytosis in macrophages [100,101]. Neutrophil apoptosis, which in combination with efferocytosis constitutes a crucial step toward ARDS resolution and is usually delayed in ARDS, is increased by linezolid [99].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The first group received colistin (125,000 UI/kg, every 6 h; 500,000 UI/ kg/day) 30 . The second group received linezolid (50 mg/kg, every 12 h) 31 . The third group received the combination of colistin (125,000 UI/kg, every 6 h) and linezolid (50 mg/kg, every 12 h).…”
Section: Study Groupsmentioning
confidence: 99%